A Note on Simple MSV Solution Methods for Rational Expectations Models of Monetary Policy. - Mash, R (Department of Economics (University of Oxford), 2003)
We analyse the derivation of optimal monetary policy under discretion and commitment when lagged expectations appear in the Phillips curve, making use of the comparatively simple MSV approach which does not require transformation of the model into state-space form.